Manual de procedimiento para la compra del cacao en el centro de acopio “Fortaleza del Valle” cantón Bolívar - Delgado Cedeño, María Annabel (2013)
Present investigation of thesis named PROCEDURAL MANUAL FOR THE PURCHASE Of COCOA IN THE COLLECTION CENTER FORTALEZA DEL VALLE IN BOLIVAR CANTON for the improvement of the purchase of cocoa in the collection center primarily. In order to get this purpose, a current analysis of the situation was done, using deductive and inductive method, field and bibliographic investigation, and polls addressed to the producers and interview directed to company employees, to diagnose the internal and external factors that affect the purchase of cocoa. It was obtained in the diagnosis that the internal factors are: Climate, quality, the cost and technology, while the external factors are: Request, taxes, the climatic phenomena, the appearing of new plagues and diseases. Activities were determined for the know how manual, materialized in a flow chart, suit as guide to speed up the process of quality control of the cocoa. The structure of the operations, for the design of the manual, with the intention of accomplishing the activities related with the improvement of purchase was defined. Therefore, with the application of the manual it will contribute in: The improvement of the purchase of cocoa, training of the producers and staff of the center in handling plagues and diseases, how to realized quality control of the product and the adequate handling of organic products.